2020
DOI: 10.1073/pnas.2008306117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical injuries of neurons induce tau mislocalization to dendritic spines and tau-dependent synaptic dysfunction

Abstract: Chronic traumatic encephalopathy (CTE) is associated with repeated traumatic brain injuries (TBI) and is characterized by cognitive decline and the presence of neurofibrillary tangles (NFTs) of the protein tau in patients’ brains. Here we provide direct evidence that cell-scale mechanical deformation can elicit tau abnormalities and synaptic deficits in neurons. Using computational modeling, we find that the early pathological loci of NFTs in CTE brains are regions of high deformation during injury. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 72 publications
1
39
0
Order By: Relevance
“…Another option, supported by recent evidence, is that some tau is physiologically present in dendritic spines [ 174 ], and that this proportion of tau is the one that mediates LTD, exerting its function in synaptic plasticity. In addition, mechanical injuries of neurons lead to mislocalization of tau to dendritic spines and tau-dependent synaptic dysfunction, mediated by GSK-3 (and CDK5) tau phosphorylation [ 179 ]. In neurodegenerative disorders such as AD and other dementias, tau becomes hyperphosphorylated, detaches from MTs.…”
Section: Interplay Between Gsk-3 and Tau During Ltdmentioning
confidence: 99%
“…Another option, supported by recent evidence, is that some tau is physiologically present in dendritic spines [ 174 ], and that this proportion of tau is the one that mediates LTD, exerting its function in synaptic plasticity. In addition, mechanical injuries of neurons lead to mislocalization of tau to dendritic spines and tau-dependent synaptic dysfunction, mediated by GSK-3 (and CDK5) tau phosphorylation [ 179 ]. In neurodegenerative disorders such as AD and other dementias, tau becomes hyperphosphorylated, detaches from MTs.…”
Section: Interplay Between Gsk-3 and Tau During Ltdmentioning
confidence: 99%
“…Several studies have also used in vitro platforms to investigate the potential mechanisms by which cell injury can lead to tau-related pathologies. For example, in one such study a stretch model employing rodent hippocampal cells was used to investigate the effect of injury on tauopathy ( Braun et al, 2020 ). This study revealed that mechanical stretching of cultured neurons resulted in tau mislocalization to dendritic spines which results in subsequent synaptic dysfunction.…”
Section: In Vitro Models Of Traumatic Brain Injurymentioning
confidence: 99%
“…Traumatic brain injury (TBI) is the strongest environmental risk factor for the accelerated development of neurodegenerative processes. Computational modelling provided insights into the cognitive decline and the presence of neurofibrillary tangles of the protein tau in the brains upon repetitive TBI [ 87 ]. The impacting high-strain rate deformation alone could induce tau mislocalization to dendritic spines and synaptic deficits in cultured hippocampal neurons which was inhibitable on the signalling level [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computational modelling provided insights into the cognitive decline and the presence of neurofibrillary tangles of the protein tau in the brains upon repetitive TBI [ 87 ]. The impacting high-strain rate deformation alone could induce tau mislocalization to dendritic spines and synaptic deficits in cultured hippocampal neurons which was inhibitable on the signalling level [ 87 ]. Thus, a mechanistic pathway directly relating mechanical deformation of neurons to tau-mediated synaptic impairments and a potential exploitable therapeutic approach to improve repetitive TBI consequences has now been provided [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation